The Shock Characteristics of Tilted Support Spring Packaging System with Critical Components - An-Jun Chen (Shock and Vibration)
The nonlinear dynamical equations of tilted support spring packaging system with critical components were obtained under the action of half-sine pulse. To evaluate the shock characteristics of the critical components, a new concept of three-dimensional shock response spectrum was proposed. The ratio of the maximum shock response acceleration of the critical components to the peak pulse acceleration, the dimensionless pulse duration, and the frequency parameter ratio of system or the angle of tilted support spring system were three basic parameters of the three-dimensional shock response spectrum. Based on the numerical results, the effects of the peak pulse acceleration, the angle of the tilted support spring, the frequency parameter ratio, and the mass ratio on the shock response spectrum were discussed. It is shown that the effects of the angle of the tilted support spring and the frequency ratio on the shock response spectrum are particularly noticeable, increasing frequency parameter ratio of the system can obviously decrease the maximum shock response acceleration of the critical components, and the peak of the shock response of the critical components can be decreased at low frequency ratio by increasing mass ratio.